2010
DOI: 10.1002/term.249
|View full text |Cite
|
Sign up to set email alerts
|

Porous polylactide/β-tricalcium phosphate composite scaffolds for tissue engineering applications

Abstract: Porous polylactide/beta-tricalcium phosphate (PLA/beta-TCP) composite scaffolds were fabricated by freeze-drying. The aim of this study was to characterize these graded porous composite scaffolds in two different PLA concentrations (2 and 3 wt%). Also, three different beta-TCP ratios (5, 10 and 20 wt%) were used to study the effect of beta-TCP on the properties of the polymer. The characterization was carried out by determining the pH, weight change, component ratios, thermal stability, inherent viscosity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Porous β-TCP/ alginate-gelatin hybrid scaffolds that were cell-compatible and possessing some osteoinductive properties were aso prepared and successfully tested in vitro. 471 Biocomposites of β-TCP with PLLA [462][463][464] and PLGC 465 were prepared as well. Although β-TCP was able to counter the acidic degradation of the polyester to some extent, it did not prevent a pH drop down to ~6.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Porous β-TCP/ alginate-gelatin hybrid scaffolds that were cell-compatible and possessing some osteoinductive properties were aso prepared and successfully tested in vitro. 471 Biocomposites of β-TCP with PLLA [462][463][464] and PLGC 465 were prepared as well. Although β-TCP was able to counter the acidic degradation of the polyester to some extent, it did not prevent a pH drop down to ~6.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Both dense and porous composites based on β-TCP have been demonstrated to show excellent performance in the physiological environment and possess several advantages over other calcium phosphates especially with regard to bioresorption [31][32][33][34][35][36]. In contrast only a few papers have been published on the fabrication of electrospun biodegradable hybrid fiber meshes containing β-TCP as inorganic component.…”
Section: Introductionmentioning
confidence: 99%
“…It remains controversial whether β-TCP can buffer acid products. Haaparanta et al 23 fabricated PLA/β-TCP scaffolds using a similar method to ours: they studied composite scaffolds containing 5, 10, and 20 wt% of mβ-TCP, and they reported that there was no significant buffering effect of β-TCP on the pH of the degradation medium in all groups. However, many studies, including the present study, have shown a pH buffering effect of β-TCP in PLA composite materials.…”
Section: Discussionmentioning
confidence: 87%